Value chain analysis of poultry in Adwa Wereda, Central Zone of Tigray, Ethiopia - Gebremedhin, G. (Aksum University, 2015)
This study was initiated to analyze poultry value chain in Adwa wereda, central zone of Tigray region. The specific objectives were to map poultry value chain functions, to determine the profit margin of actors along the poultry value chain, to identify factors that determine poultry market participation decision and its supply to the market and to identify major constraints and opportunities along poultry value chain. The data were collected from individual farmer using questionnaire. A total of 200 poultry producing sample households from four potential poultry producing Tabias of the wereda were surveyed. Descriptive statistics such as t-test and chi-square were employed to examine the existence of statistically significant differences between the poultry market participants and non-participants. Moreover, margin analysis was used to calculate the marketing margin of participants and traders along the poultry value chain in the study area. The major marketing channels and main actors involving in the market were identified. Marketing channels of egg and chicken indicated a shorter path. The major market actors in the survey period were producers, collectors, wholesalers, retailers and consumers. To evaluate poultry market performance cost, profit and marketing margins were calculated for the group of market players in different channels. The producer’s share of the total consumer price and the total gross marketing margin were 100% and zero in channel I respectively. Heckman two stage econometric model was used to identify factors determining market participation decision and value of poultry sales. Results obtained from the first stage of the model indicated that sex of the household head, number of chickens owned and extension contact were the variables that influenced the decision to participate in poultry and egg market positively while distance to the wereda market influenced the decision to participate in poultry and egg market negatively. Results from second stage of the model shows that the number of chickens owned and access to extension contact influenced the value of poultry sales by the market participants positively while distance to the wereda market and exotic poultry breed influenced volume of poultry sold by the participants negatively. Results from second stage of the model also shows that, number of poultry owned, access to credit, exotic poultry breed, education status and years of experience in farming influenced the value of egg sales positively while age of the household head were found to be influence egg supply to the market negatively. Poultry production was constrained by diseases, extension service, limited supply of exotic chicken, poor housing and feeding systems. Some of the diseases identified by the sample households were new castle, avian pasterolosis, coccidosis, Salmonellosis, pulorum disease and fowl pox. Traders were also constrained by lack of poultry and egg supply, trade license and diseases. In spite of this, it had also opportunities such as high turnover earning, small feed and space requirement, lower initial cost requirement, and employment opportunities. Therefore, raising awareness and capacity building of both farmers and DAs on how to manage poultry and incorporate new technologies, market information and modern inputs are the actions to be taken to strengthen the sector’s contribution to the wereda’s economic development.